Comparing visual and auditory working memory in adults with stutter and normal adults - Elham Hakimi; Ali Ghanaei Chamanabad; Javad Salehi Fadardi; Saeedeh Hajebi (فصلنامه علمی- پژوهشی اصول بهداشت روانی)
Introduction: Developmental stuttering is a neurological disorder commonly manifested as a motor problem. Cognitive theories, however, hold that poorly developed cognitive abilities are the origins of stuttering. This study aimed to compare the visual and auditory working memory in adults with and without stutter.